Preventive treatment response associated with migraine aura subtypes in a Thai population - Asawavichienjinda, Thanin; Storer, Robin James (Frontiers in Human Neuroscience, 2023)
Some studies indicate a different response to treatment between migraine patients with and without aura. To determine whether aura, or simple or complex aura subtypes, are clinical markers predicting response to preventive treatment, we conducted a retrospective cohort study at a headache clinic in a tertiary referral hospital. We included data from patients registered from November 1, 2014, to June 30, 2022, having migraine with or without aura, or with simple or complex aura, and who had received migraine preventive treatments with at least 3 months follow-up. The primary outcome was a response to preventive treatment defined as at least a 50% reduction from a baseline of monthly migraine or headache days (MMDs/MHDs). Secondary outcomes were improvement in quality of life and disability scores. For migraine patients with (45) and without (123) aura who took a migraine preventive with at least 3 months follow-up; except for median age, which was older for patients without aura, baseline sex, comorbidity, and migraine data were without significant difference including median history of migraine, chronic migraine subtype, chronic migraine with medication-overuse headache, median or mean MMDs/MHDs, number of preventive medications used, or migraine prevention medication inhibiting spreading depolarizations. Treatment outcomes at 3 and 6 months follow-up were not significantly different between migraine patients with and without aura, or with simple and complex aura, but tended to be greater in those with aura and those with complex aura. After adjustment for baseline comorbidity, migraine subtypes, aura subtypes, the number of preventives used, history of migraine, and MMDs/MHDs, we found no significant differences in 30% and 50% reduction from baseline of MMDs/MHDs in 3 or 6 months or most recent follow-up. Preventive treatment response tended to be associated with migraine aura subtypes. We found preventive treatment response tended to have more favorable outcomes in those with aura, especially those with complex aura.